Phytochemical constituents and preliminary toxicity evaluation of leaves from Rourea induta Planch. (Connaraceae) - Milena Kalegari; Marilis Dallarmi Miguel; Josiane de Fátima Gaspari Dias; Ana Luísa Lacava Lordello; Cristina Peitz de Lima; Cristina Mayumi Sasaki Miyazaki; Sandra Maria Warumby Zanin; Maria Christina dos Santos Verdam; Obdulio Gomes Miguel (Universidade de São Paulo, 2011)
Most active plants are toxic at high doses and it is therefore important to investigate the preliminary toxicity of plant extracts. The Rourea induta species is a potential drug with no phytochemical or biological studies registered in the literature. Thus, a phytochemical study and a toxicity analysis of the ethanolic extract obtained from the leaves of Rourea induta Planch., Connaraceae, was run. A long chain hydrocarbon, n-tetracosane, and four flavonoids were identified: quercetin, and three glycosylated derivates, quercetin-3-O-α-arabinofuranoside, quercetin-3-O-β-xyloside and quercetin-3-O-β-galactoside. This is the first time these have been isolated in this species. The structures were elucidated by 13C NMR, ¹H NMR, UV and IR spectroscopy. The toxicity evaluation of extracts was performed by the brine shrimp method and determination of hemolytic activity. The samples demonstrated no toxic potential by the analyzed methods. A maioria das plantas ativas é tóxica em doses elevadas, portanto, é importante a investigação da toxicidade preliminar dos extratos das plantas. A espécie Rourea induta é uma droga potencial que não apresenta estudo fitoquímico ou biológico descrito na literatura. Assim, um estudo fitoquímico e análises toxicológicas foram realizados com o extrato etanólico obtido das folhas de Rourea induta Planch., Connaraceae. Foram obtidos um hidrocarboneto de cadeia longa, n-tetracosano, e quatro flavonóides, quercetina e três derivados glicosilados, quercetina-3-O-α-arabinofuranosideo, quercetina-3-O-β-xilosideo e quercetina-3-O-β-galactosideo. Esta é a primeira vez que estes compostos são isolados nesta espécie. As estruturas foram elucidadas por espectroscopia de RMN-13C, RMN-¹H, ultravioleta e infravermelho. A avaliação da toxicidade dos extratos foi analisada pelo método da Artemia salina e atividade hemolítica. Nenhuma das amostras testadas apresentou um potencial tóxico pelos métodos analisados.